(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objectives: The objective of the study was to find out the efficacy and safety of misoprostol in termination of missed abortion. Materials and Methods: This was a prospective study carried out during the time from August 2009 to April2010 in Dhaka Medical College Hospital. Results: A total 50 cases of missed abortion (12-28weeks) were included in the study. Tab.misoprostol(2oo?gm) was used pervaginally 4hourly for termination of pregnancy. Maximum 4tab.were used. Outcome variables were doses of misoprostol, expulsion times need for use of oxytocin and D and C and side effect of misoprostol. In the present study, 58% percent (29 out of 50 ) experienced complete expulsion (20% after 1st dose, 24% after 2nd dose 24% after 3rd dose and, 31% after 4th dose).24% cases needed oxytocin drip as an adjunct and 18% needed surgical evacuation when 4 doses of misoprostol (tab cytomis)and oxytocin fail to expel the product of conception. Mean (±SD) time required for expulsion of product of conception was 11.44 ± 4.43 hours in 29 (58%) women who were given tab misoprostol only. The results showed that 5(out of 25) has a complete expulsion after first dose, 13 after second 4 after 3rd and Mean induction expulsion time was 6.1 hours The most common complication was temperature 6%, vomiting 4%, and diarrhoea 2%. Conclusion: Vaginal application of misoprostol can be used to women with missed abortion for complete expulsion of the product of conception and may reduce the need for surgical intervention. DOI: http://dx.doi.org/10.3329/bjog.v25i2.13742 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(2) : 65-70